The seroconversion rate of QuantiFERON-TB gold in-tube test in psoriatic patients receiving anti-interleukin-23 monoclonal antibodies - Yi-Wei Huang; Tsen-Fang Tsai (Wolters Kluwer Medknow Publications, 2022)
Background: Biologic therapies have become the gold standard for the treatment of moderate-to-severe psoriasis and psoriatic arthritis. However, concerns for opportunistic infections exist, especially for tuberculosis (TB) in endemic areas. Previously, tumor necrosis factor inhibitors were reported to carry higher risks of latent TB infection (LTBI) reactivation or new active TB, followed by anti-interleukin (IL)-12/23 and IL-17 agents in Taiwan. Objectives: The objective of the study is to provide real-world clinical rate of seroconversion of serial QuantiFERON-TB gold in-tube (QFT-GIT) tests, for detection of LTBI and newly-acquired TB, in psoriasis patients while receiving IL-23 inhibitors in an intermediate TB burden country. Methods: The local risk management plan required regular monitoring of TB while receiving biologics for psoriasis. This retrospective cohort evaluated consecutive psoriasis patients who received guselkumab or risankizumab between 2015 and 2021 in a tertiary referral center in Taiwan. Results: A total of 144 patients were included, with negative baseline QFT-GIT in 88% and positive in 13%. After receiving at least 6 months of anti-IL-23 drugs, persistently seropositive was found in 15 patients (10%), persistently seronegative in 125 patients (87%), seroconversion in 1 patient (0.6%), and seroreversion in 3 patients (1.9%). The seroconversion rate was 1% (1/127) in individuals under anti-IL-23 medications for at least 12 months. No case of LTBI reactivation was identified. Conclusion: In psoriasis patients under anti-IL-23 therapy, serial interferon-gamma release assays demonstrated a low seroconversion rate (<1%). Anti-IL-23 agents may be a favorable choice for psoriasis patients with a higher risk of TB infection and LTBI reactivation or those who reside in endemic regions.